Coagulopathy in dengue fever patients - Kannan, Abhilash; Narayanan, Kala Syamalakumari; Sasikumar, Sheetal; Philipose, Jobin; Surendran, Sreerag Alumparambil (International Journal of Research in Medical Sciences, 2017)
Background:The study was done to find out the prevalence of coagulopathy in Dengue fever patients with thrombocytopenia and its clinical significance. Methods:The patients admitted in medical wards and ICU were included in the study after considering certain inclusion and exclusion criteria. APTT, PT & D-dimer assays were also done in the study population. Coagulopathy was considered when APTT values were ≥41seconds. Results:22.3% of the study population showed evidence of coagulopathy. Bleeding manifestations significantly increased with increasing APTT values. There is also significant association between platelet counts and bleeding manifestations. As platelet count falls there is a tendency for APTT to rise. Conclusion:In addition to thrombocytopenia, coagulopathy also contribute to the presence of bleeding manifestations in dengue fever patients. There is a significant correlation between bleeding manifestations with abnormal APTT values. As platelet count decreases there is tendency for rise in APTT values.